MAKNA KAOMOJI YANG DIGUNAKAN PADA MEDIA SOSIAL SERTA FUNGSINYA DALAM KALIMAT BAHASA JEPANG - Vestika Lona; Nana Rahayu; Zuli Laili Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This research’s goal is to know the meaning of kaomoji in social media especially facebook. This research object are members of facebook group which uses kaomoji in post or comments whose data a sentence use of kaomoji. This research used descriptive and qualitative approach to analyze object based on theories used. The research datas taken by read post or comments facebook groupst. Author use politeness strategies theory by Charles Sander Peierce. This research result show the meaning of kaomoji at social media has the function confirmation and subtitute the verbal element in sentence. This research could be the basis for further studies involving more subjects to ensure the generalizability of the results.Keywords: kaomoji, semantic, social media